Tecnologias digitais na educação física: o celular enquanto instrumento de ensino e aprendizagem - Fábio Souza de Oliveira (2020)
In view of the strong presence of the smartphones in the context of basic school, this study aimed to investigate how the cell phone, from the point of view of teaching and learning can be used in the context of school Physical Education classes. From the central objective of the study, we derive the following specific objectives: Map the different uses and relationships between the students of this research and their smartphones; Identify the uses of cell phones by students in the personal, school and Physical Education context; Analyze with the students of the final years of elementary school, the possible uses of the cell phone as a teaching and learning tool in the context of school Physical Education. This study is justified because we understand how much the media content is responsible for the social representations built by young people of school age and because there is currently great difficulty in basic education, particularly in the final years of elementary school, in materializing a critical-reflective proposal about this thematic. For such, we developed a research with a qualitative approach, involving several instruments and research techniques. Initially, we carried out an exploratory mapping from the application of questionnaires to students of the eighth and ninth grade, aged between 13 and 17 years old. During our stay in the empirical field, the field diary was the privileged instrument in the sense of recording facts, impressions and any other aspects that could compose a more appropriate reflective image of the studied phenomenon. Based on the data from the questionnaires, an interview script was developed that allowed for a deeper understanding of that reality. Finally, in addition, we used the images made in the empirical field for agreeing with Dussel and Gutierrez when the authors claim that this is an important tool for educational research. Along this path, the theoretical foundation was anchored in studies on media education and critical theory, based on research by Fantin (2006, 2012), Fantin and Rivoltella (2012), Belloni (2009), Martín-Barbero (2014), Zuin, Pucci and Lastória (2015), Turcke (2010) and Pucci (2016), supporting us in the discussion about the (non) place of technologies in education and about media-education in the context of school Physical Education. Among some of the considerations of this study, we can highlight: television and the internet, through the smartphone are the two main media channels of these young people, access point for a numberless of risks and possibilities. The main uses of this device among these students are access to social networks and electronic games, realities not yet properly discussed by the Physical Education. The cell phone presents itself as a powerful ally for formative proposals at school and, particularly in Physical Education, having proved to be viable for the approach of volleyball content. There is a great gap between what technologies are in the educational field, what they can and should be, spaces that can be reduced based on reflection, action and political and pedagogical attitude.